Challenges for the public use of reason in the post-truth times - Khachatryan, Lilia (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
The post-truth era presents significant obstacles to individuals’ ability to reason freely and independently and make informed decisions in the public sphere. In the article, the author draws on the 18th-century German philosopher Immanuel Kant’s concept of the public use of reason, highlighting that retreating from the values of Enlightenment threatens the future of public rational discourse and democracy. In today’s world, the Kantian idea of public use of reason faces several challenges related to moving away from or at least deviating from Enlightenment ideals. This article will address the most pressing issues of the current post-truth world: misinformation and disinformation, social media algorithms and echo chambers, emotional manipulation, and populism. Each of these factors in turn undermines the necessary conditions for individuals to reason freely and independently in the public sphere. However, by revising the goals of education, rebuilding trust in traditional institutions, implementing more thoughtful strategies around digital technologies, and prioritizing the "big" politics of public truths, it is still possible to create public spaces for free deliberation and democratic engagement.